The Philippine press and ASEAN's non-interference policy a content analysis on the articles published during the 31st ASEAN ministeral meeting in ASEAN's non-interference policy as covered by five Philippine dailies - Pioquinto, Kathyrin Fe D'Lonsod
This research is a content analysis on the articles published during the 31st ASEAN Ministerial Meeting on ASEAN's "non-interference policy" as covered by five selected newspapers namely: TODAY, Philippine Daily Inquirer, The Manila Times, Philippine Star and Manila Bulletin. This study examined the role of the Philippine press in voicing out the stand of the Philippines on the non-interference policy during the 31st AMM. The articles were examined by determining their emphasis and slant through their factuality, completeness and impartiality. Stuart Hall's theory of hegemony may well explain that since the nature of society is reflected on the press, it is imperative that the press would handle the news in a way that would be representative of the kind of government it belongs. ASEAN is ruled by consensus and the ruling ideology will win over the issue. But the Philippine press is "ruled," in this case, by the Philippine stand. Findings proved that all the five national dailies have a nationalistic (patriotic) and ethnocentric bias in the choice of topics and opinions expressed. It also indicated that the five national dailies uncharacteristically agreed that the Philippines took the right side on the issue. This was evidenced by the way they handled the contention. The five dailies presented the factual reports but gave more emphasis on the Philippine stand.